ANALYSIS REPORT FINANCE PT. INDOFOOD SUKSES MAKMUR TBK PERIOD 2020-2024 - Salsabila Azzahra Haryu Putri; Mutiara Andini; Putri Nabila; Miftahul Jannah; Ratna (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Financial performance is an essential indicator for assessing a company’s financial health and business sustainability amid increasingly dynamic competition. This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk using a financial ratio analysis approach. The research employs a descriptive quantitative method, utilizing secondary data derived from the company’s officially published financial statements. The analytical techniques applied include liquidity, solvency, and profitability ratios to evaluate the company’s ability to meet its short-term and long-term obligations as well as to generate profits. The results indicate that PT Indofood Sukses Makmur Tbk demonstrates a relatively strong level of liquidity, reflecting its capability to fulfill short-term liabilities. In terms of solvency, the company shows a fairly stable capital structure, although it remains partially dependent on debt financing for its operations. Meanwhile, profitability ratios reveal fluctuations in earnings performance, influenced by both economic conditions and operational factors. Overall, the findings suggest that the financial performance of PT Indofood Sukses Makmur Tbk is in a generally good condition; however, the company is encouraged to improve asset and capital efficiency to ensure sustainable financial performance in the future. This study is expected to provide valuable insights for management evaluation and serve as a reference for investors and future researchers.